2007
DOI: 10.1016/j.jmwh.2007.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Lactation Complicated by Overweight and Obesity: Supporting the Mother and Newborn

Abstract: Research shows that mothers who are obese (with a BMI >30) are less likely to initiate lactation, have delayed lactogenesis II, and are prone to early cessation of breastfeeding. Black women, with the highest rates of American obesity, have the lowest rates and shortest duration of breastfeeding compared to Hispanic and white women. Women who are overweight and obese have lowered prolactin responses to suckling. Women who are obese are at risk for prolonged labors, excessive labor stress, and cesarean birth, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
83
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 42 publications
0
83
0
3
Order By: Relevance
“…Obese women tend to have larger breasts, with an excess of periareolar adipose tissue which may flatten the areola and nipple, making the nipple more difficult for the newborn to grasp. This difficulty contributes to the reduced prolactin response to suckling (Coates, 1989;Jevitt, Hernandez & Groer, 2007;Lovelady, 2005).…”
Section: Delayed Onset Of Lactation Andmentioning
confidence: 99%
“…Obese women tend to have larger breasts, with an excess of periareolar adipose tissue which may flatten the areola and nipple, making the nipple more difficult for the newborn to grasp. This difficulty contributes to the reduced prolactin response to suckling (Coates, 1989;Jevitt, Hernandez & Groer, 2007;Lovelady, 2005).…”
Section: Delayed Onset Of Lactation Andmentioning
confidence: 99%
“…Obese women tend to have larger breasts, with an excess of periareolar adipose tissue which may flatten the areola and nipple, making the nipple more difficult for the newborn to grasp. This difficulty contributes to the reduced prolactin response to suckling (Coates, 1989;Jevitt, Hernandez & Groer, 2007;Lovelady, 2005 Low maternal self-esteem and selfconfidence, and reduced belief in their ability to breastfeed are two of the strongest predictors of breastfeeding cessation.…”
Section: Delayed Onset Of Lactation Andmentioning
confidence: 99%
“…Fewer obese mothers felt that their milk supply was sufficient at one month and three months compared to normal weight women (Mok et al, 2008). This challenge has been recognised with some midwifery care plans identifying overweight and obese women as needing extra support due to their reduced perceptions of breast fullness and milk production (Jevitt et al, 2007). Research examining lactation-counselling practices used with obese mothers (Rasmussen, Lee, Ledkovsky & Kjolhede, 2006) found that the majority of health care providers surveyed neither believed that there was a difference in the success rate between obese mothers and normal weight mothers, nor advised obese mothers differently about breastfeeding (Rasmussen et al, 2006).…”
Section: Delayed Onset Of Lactation Andmentioning
confidence: 99%
See 2 more Smart Citations